Răspuns :
[tex]\frac{1}{3} \ din \ x= \frac{1}{4} * y \\\\ \frac{x}{3}=\frac{y}{4}= k \\\\ x=3k \\ y=4k \\\\ x+y=63 \\\\ 3k+4k=63 \\\\ 7k=63 \ |:7 \\\\ \boxed{k=9} \\\\ x=3*9 \\\\ \boxed{\boxed{x=27}} \\\\ y=4*9 \\\\ \boxed{\boxed{y=36}}[/tex]
a+b=63
a/3=b/4 rezulta ca a=3b/4 inlocuim in prima
3b/4+b=63 aducem la acelasi numitor comun
3b/4+4b/4=63
7b/4=63
b=63:7/4
b=63x4/7 simplificam 7 cu 63
b=9x4
b=36
a=3b/4=3x36totul supra 4
a=27
a/3=b/4 rezulta ca a=3b/4 inlocuim in prima
3b/4+b=63 aducem la acelasi numitor comun
3b/4+4b/4=63
7b/4=63
b=63:7/4
b=63x4/7 simplificam 7 cu 63
b=9x4
b=36
a=3b/4=3x36totul supra 4
a=27